2006
DOI: 10.1211/jpp.58.4.0006
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of trans-resveratrol by human liver and intestinal microsomes and UGT isoforms

Abstract: Resveratrol (trans-resveratrol, trans-3,5,4'-trihydroxystilbene) is a naturally occurring stilbene analogue found in high concentrations in red wine. There is considerable research interest to determine the therapeutic potential of resveratrol, as it has been shown to have tumour inhibitory and antioxidant properties. This study was performed to investigate the glucuronidation of resveratrol and possible drug interactions via glucuronidation. Two glucuronide conjugates, resveratrol 3-O-glucuronide and resverat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 52 publications
7
81
0
Order By: Relevance
“…Other studies have shown low or no UGT expression in normal human lung tissue (Zheng et al, 2002;Somers et al, 2007;Nakamura et al, 2008). In the present study, the absence of R3G formation in human lung fraction is consistent with low or absent expression of UGT isoforms in normal human lung tissue (Nakamura et al, 2008) responsible for RES glucuronidation (Brill et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Other studies have shown low or no UGT expression in normal human lung tissue (Zheng et al, 2002;Somers et al, 2007;Nakamura et al, 2008). In the present study, the absence of R3G formation in human lung fraction is consistent with low or absent expression of UGT isoforms in normal human lung tissue (Nakamura et al, 2008) responsible for RES glucuronidation (Brill et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…First-pass metabolism by gut, liver, and lungs in series can synergistically increase total body clearance of RES. Although the role of gut and liver in the metabolism of RES is known (Miksits et al, 2005;Brill et al, 2006;Iwuchukwu and Nagar, 2008), the contribution of lungs to RES metabolism has not been evaluated. In the present study, the contribution of lungs in the metabolism of RES was evaluated using multiple sites of administration and a single site of sampling design (Cassidy and Houston, 1980) in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on flavonoid content in grape seeds of 4 to 5 %, in vivo quercetin and kaempferol concentrations are not likely to reach inhibitory levels [79]. Resveratrol is also a substrate for UGT1A1 and UGT1A9 enzymes, but no information is available on its potential to modulate UGT enzymes [54,55]. In rats, catechin glucuronides were the primary existing form of catechins in plasma following oral grape seed extract administration [80].…”
Section: Grape Seedmentioning
confidence: 99%